Rigid‐layer Raman‐active modes in N‐layer transition metal dichalcogenides: interlayer force constants and hyperspectral Raman imaging. (23rd October 2017) - Froehlicher, Guillaume; Lorchat, Etienne; Zill, Olivia; Romeo, Michelangelo; Berciaud, Stéphane
Abstract : We report a comparative study of rigid‐layer Raman‐active modes in N ‐layer transition metal dichalcogenides. Trigonal prismatic (2Hc, such as MoSe2, MoTe2, WS2, and WSe2 ) and distorted octahedral (1T', such as ReS2 and ReSe2 ) phases are considered. The Raman‐active in‐plane interlayer shear modes and out‐of‐plane interlayer breathing modes appear as well‐defined features with wavenumbers in the range 0−40cm −1 . These rigid‐layer modes are well described by an elementary linear chain model from which the interlayer force constants are readily extracted. Remarkably, these force constants are all found to be of the same order of magnitude. Finally, we show that the prominent interlayer shear and breathing mode features allow high‐precision hyperspectral Raman imaging of N ‐layer domains within a given transition metal dichalcogenide flake. Copyright © 2017 John Wiley & Sons, Ltd. Abstract : We report a comparative study of rigid‐layer Raman‐active modes in N ‐layer transition metal dichalcogenides. Trigonal prismatic (2Hc, such as MoSe2, MoTe2, WS2, and WSe2) and distorted octahedral (1T', such as ReS2 and ReSe2) phases are considered. The Raman‐active in‐plane interlayer shear modes and out‐of‐plane interlayer breathing modes appear as well‐defined features with wavenumbers in the range 0–40 cm −1 . These rigid‐layer modes are well described by an elementary linear chain model from which the interlayer force constants are readily extracted. Remarkably, these force constants are all found to be of the same order of magnitude. Finally, we show that the prominent interlayer shear and breathing mode features allow high‐precision hyperspectral Raman imaging of N ‐layer domains within a given transition metal dichalcogenide flake.